North-facing elevation of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The north-facing elevation of the Suhaveshwar Temple is identical to the south-facing side. The protruding shukanasa, the front of the shikhara (superstructure), is visible here. It is a semi-circular opening. The topmost portion of the main shikhara is missing. Along the elevation of the temple, the mandapa (pillared hall) shikhara has a row of large ghantikas (aedicules) that cascade from the centre. The base of the mandapa shikhara has a square block with diamond motifs that is topped by a gavaksha (dromer window) design.